A new species of Leitoscoloplos and redescription of Scoloplos tumidus Mackie, 1991 (Polychaeta, Orbiniidae) from Chinese coastal waters - Yue Sun; Boping Tang; Xinzheng Li (Frontiers in Marine Science, 2026)
We described Leitoscoloplos fangchengensis sp. nov., a new species of orbiniid polychaete from Fangchenggang City, Guangxi Province, Beibu Gulf. The species differs from all congeners by the distinctive membranous pouches located below and posterior to neuropodial lobes on the last thoracic and abdominal chaetigers. We also re−examined material previously identified as Scoloplos marsupialis Southern, 1921 and found that these correspond to Leodamas weizhouensis Sun et al., 2022 and S. tumidus Mackie, 1991. A detailed redescription of S. tumidus Mackie, 1991 was here provided based on Chinese material, together with a table summarizing all known orbinid species bearing membranous pouches. With this study, we are contributing to clarify long-standing taxonomic confusion within Orbiniidae.